Kepastian Hukum Penyelesaian Sengketa Gagal Bayar P2P Lending di Indonesia - Muhammad Salman Al Farizi Putra Artansya; Jamal Wiwoho (Indonesian Journal of Social Sciences and Humanities, 2026)
The development of peer-to-peer lending (P2P lending) as part of financial technology has increased access to financing, but also creates legal risks in the form of default, which are detrimental to lenders. This study aims to analyze legal certainty in resolving default disputes in P2P lending in Indonesia and examine the legal remedies available to lenders. This research is a normative legal study with a statutory and conceptual approach, utilizing primary and secondary legal materials analyzed qualitatively through deductive reasoning. The results indicate that default can be legally qualified as a breach of contract, which entitles lenders to demand fulfillment of obligations or compensation. Furthermore, dispute resolution is carried out in stages through internal platform mechanisms, non-litigation, and litigation. Although regulations have provided formal legal certainty, in practice, weaknesses remain in the protection aspect for lenders, primarily due to the use of standard electronic contracts and the unequal position of the parties. Therefore, legal certainty in P2P lending needs to be interpreted not only as clarity of norms but also as a guarantee of substantive protection for injured parties.